Model of Communication Policy on the Development of the City without Slum (KOTAKU) Medan City - Yusnadi, Yusnadi; Lubis, Lahmuddin; Nuraflah, Cut Alma (Budapest International Research and Critics University, 2019)
The purpose of this study is to describe the model of communication policy on the development of the city without slum (Kotaku). The method which is used in this study was descriptive qualitative approach. This study is located in Medan Area sub district and Medan Helvetia sub district, Medan city. The informants were six people, consisting of three Kotaku facilitators, two leader of the Community Self-Help Agency (BKM) and one person from the Government (Dinas PUPR). Techniques of collecting data through the interview process using (semi-structured) interview guides, observation and document tracking. Techniques of analyzing data is used by Miles & Huberman model, starting with data reduction, data display and conclusion drawing/ verification. Check the validity of the data by using triangulation. The results shows that the model of communication policy on the development of the city without slum (Kotaku) Medan City uses a linear communication model where all policies related to planning the communication policy on the development of the city without slum (Kotaku) Medan city are carried out by the Government based on three things: the 1945 Constitution, Presidential Decree and Mayor's Decree.